THE RIGHT MIX OF APPROACHES IN THE ENGLISH LANGUAGE TEACHING: ACHIEVING DESIRED LEARNING OUTCOMES IN THE ESP CLASSROOM - Topuzov, Oleh; Malykhin, Oleksandr; Aristova, Nataliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The proposed study is focused on solving research questions concerning a common understanding of methodology in teaching English for Specific Purposes and language teaching approaches application in instruction process. The novelty of the paper lies in the theoretical substantiation of the necessity to apply the combination of competence-based, action-oriented and blended-learning approaches in the ESP classroom for improving ESP students’ languages competence regarded in our study as desired learning outcomes. The research is theoretical in nature and comprises the theoretical review of scientific literature aimed at understanding how methodology is conceived by scientists and ESP practitioners. The theoretical review contains the analysis of scientific publications and methodological materials on teaching English for Specific Purposes at higher education institutions. The authors also analyze the most trusted language teaching approaches, principles they are based on, learning outcomes they are aimed at in the ESP classroom, the advantages and disadvantages of their use in instruction process. The analysis of the most trusted language teaching approaches makes it possible to declare that the combination of competence-based, action-oriented and blended-learning approaches plays a crucial role in providing ESP students with improved languages competence.